Advances in targeting tumor microenvironment for immunotherapy - Wang, Lugang; Zhang, Liubo; Zhang, Zhen; Wu, Peng; Zhang, Yi; Chen, Xinfeng (Frontiers in Immunology, 2024)
The tumor microenvironment (TME) provides essential conditions for the occurrence, invasion, and spread of cancer cells. Initial research has uncovered immunosuppressive properties of the TME, which include low oxygen levels (hypoxia), acidic conditions (low pH), increased interstitial pressure, heightened permeability of tumor vasculature, and an inflammatory microenvironment. The presence of various immunosuppressive components leads to immune evasion and affects immunotherapy efficacy. This indicates the potential value of targeting the TME in cancer immunotherapy. Therefore, TME remodeling has become an effective method for enhancing host immune responses against tumors. In this study, we elaborate on the characteristics and composition of the TME and how it weakens immune surveillance and summarize targeted therapeutic strategies for regulating the TME.